An Analysis Of The Influence Of E-Commerce And The Rupiah Exchange Rate On Indonesia's Economic Growth - Rafika Santri; Mohammad Yusuf; Sanusi Ghazali Pane (Jurnal Scientia, 2024)
This research aims to analyze the influence of E-Commerce and the Rupiah Exchange Rate on Indonesia's Economic Growth in the 2019-2023 period. Using quantitative descriptive research methods with timeseries secondary data analyzed via SPSS software, this research tests three main hypotheses: the significant influence of E-Commerce on economic growth, the significant influence of the Rupiah Exchange Rate on economic growth, and the simultaneous influence of E-Commerce and the Rupiah Exchange Rate to economic growth. The analysis results show that individually, E-Commerce does not have a significant influence on economic growth, with a sig value of 0.689 (>0.05). Meanwhile, the Rupiah Exchange Rate shows a significant and negative influence on economic growth, with a sig value of 0.022 (<0.05), which means that Rupiah depreciation tends to reduce economic growth. Simultaneously, these two variables show a significant influence on economic growth with a sig value of 0.038 (<0.05) and an R² of 0.962, indicating that the combination of these two variables can explain 96.2% of the variability in Indonesia's economic growth.